Cain and the book of Jonah - Lasine, Stuart (Journal for the study of the Old Testament, 2026)
Recently a number of commentators have argued that the book of Jonah consistently alludes to the exiled Cain. These allusions are taken as evidence that exile is also a main theme in Jonah, even though the book contains no explicit mention of exile. Kelsey contends that the same sense of exile exhibited in Genesis 4 ?permeates the book of Jonah?. Some scholars call Cain and Jonah ?typological figures of exile?, while others view their stories as allegories. These authors base their conclusions on verbal echoes, analogous situations, and similar characterizations. This paper argues that there is inadequate textual evidence to support these sweeping claims. The analysis begins with an assessment of the proposed verbal allusions and then moves on to alleged similarities in plot and characterization. The conclusion considers ways to assess the importance of a given intertextual allusion and comments on the current tendency to find exile in much biblical literature.